Diversity and Distribution of Anomalures and Squirrels in Oban Hills of Nigeria (2022)
The Congolian tropical forest represents the epicenter of biodiversity conservation and squirrel diversity in the Western and Central African region of sub-Saharan Africa. The scientiﬁc knowledge gap of squirr el species diversity,distribution and ecology of the region is limited. We investigated anomalure and squirrel richness and diversity in diﬀerent land-use types in the Oban region, Nigeria between January 2010 and April 2013 to update species baseline information on squirrels. In total we recorded 495 individuals of seven species and six genera representing, Anomaluridae and Sciuridae families, were detected in the Oban Hills Region. The Anomaluridae family accounted for one genus and one species (Anomalurus beecrofti),while the Sciuridae family is represented by the Xerini and Protoxerini tribes in ﬁve genera (Funisciurus, Heliosciurus, Xerus, Paraxerus, and Protexerus). Encounter rates with ﬁve diﬀerent species revealed that the Protoxerini tribe (FunisciurusanerythrusandHeliosciurusrufobrachium)werethemostfrequentlydetectedacrossallthe land-use types in the region. The high diversity of squirrels detected in the region could be a reﬂection of its recognition as a biodiversity hotspot. Also,closed-canopy cover had the highest diversity index and evenness recorded than farm fallow. Studies on population monitor in ecology and conservation help species- and site-speciﬁc conservation strategies in the region. We conclude that closed-canopy forest has high conservation value, and that management should be initiated where possible to alleviate threats to its continued functioning and eﬀort must be directed towards ascertaining the ecology and biology of squirrel species for eﬀective conservation strategies.